Uji Karakteristik Bahan Bakar Hasil Pirolisis Sampah Plastik Berjenis Low Density Polyethylene (LDPE) dengan Memvariasikan Laju Volume Air Pendingin pada Kondensor - Prasetya, Rafly Nanda; Suarnadwipa, I Nengah; Murti, Made Ricki (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract The use of plastic in Indonesia is very large. The more plastic is used in Indonesia, the more waste will be piled up. LDPE plastic is the most widely known and used type of plastic in Indonesia. Plastic waste can be converted into liquid fuel through the pyrolysis process. This effort is made to overcome the accumulation of plastic waste. Plastic waste made of low density polyethylene (LDPE) was pyrolyzed in this study. The reason for this study was to dissect the properties of the fuel produced from pyrolysis. This study uses the cooling water volume rate as a variation, namely 0.8 L/minute, 2.0 L/minute, 6.1 L/minute, 7.0 L/minute, 7.8 L/minute. LDPE plastic weighing 1000 grams, with a heating temperature of 300 °C. The results of this study indicate that the volume of oil produced from the LDPE plastic pyrolysis process increases along with the volume rate of cooling water used in the condenser. However, testing the density, viscosity, calorific value, and flash point of oil on liquid fuel from pyrolysis showed that changes in the volume rate of cooling water in the condenser did not affect the characteristics of the liquid fuel from pyrolysis. Keywords: pyrolysis, plastic waste, condenser, low density polyethylene (LDPE